Effects of Vitamin E on Chronic Haematoxicity of Paraquat Exposed Male Albino Rats (Rattus norvegicus) - Okolonkwo Benjamin Nnamdi; Jonathan Nyebuchi; Adjekuko Ohwonigho Collins; Zebedee Loveday Udu (Archives of Current Research International, 2022)
Paraquat is an environmental pollutant that is associated with some disorders including alteration of some harmatological indices and is a concern to public health. Vitamin E has antioxidant property and other characteristic roles that ameliorate toxic effect. 200 male albino rats weighing 0.2±0.02kg on the average were divided into four main groups (A, B, C, and D) with 50 rats in one group. The “A” group was not served paraquat solution and was used as the control group. Group “B”, “C”, “D” being the treatment group were given dose rates of paraquat of 0.02g, 0.04g, and 0.06g, of paraquat per kg rat respectively every two weeks for three months. The main groups further had subgroups. “A”, “A0” and “AVE”; “B”, “B0” and “BVE”; “C” had “C0” and “CVE”; and “D”, “D0” and “DVE” subgroups. Vitamin E was not given to subgroups “A0”, “B0”, “C0” and “D0” subgroups while “AVE”, “BVE”, “CVE” and “DVE” were fed orally with 500mg of vitamin E therapy every week. Treatment with vitamin E began three months after paraquat treatment. At the end of the weekly treatment with vitamin E for a month, the rats were sacrificed and their blood samples were obtained and analyzed for PCV, Hb, WBC, neutrophil and lymphocyte. A0, B0, C0 and D0 intergroup comparison was statistically significant, p-value<0.05 in PCV and Hb levels while their WBC, neutrophil and lymphocyte had no statistical significance. Ave, Be, Cve and Dve intergroup comparison was statistically significant, p-value<0.05 in PCV and Hb levels while WBC, lymphocyte and neutrophils had no statistical significance among the groups. Intra group comparison showed that only PCV and Hb were significant between groups, p-value<0.05. This study confirms that vitamin E is potent in treating paraquat toxicity in male albino rats on one month of weekly treatment.